(untitled) (Research, Society and Development, 2023)
Mozambique is greatly endowed with a diverse potential of natural resources, most of which are still unexploited or in an exploration phase. However, the country faces major challenges to make better use of the resources to feed the population and reduce poverty. The country is prone to recurrent natural disasters, such as: flooding and cyclones (north) and droughts (south). Between 2019 to 2021, Sussundenga District was punctuated by two severe tropical cyclones – Idai and Eloise – leaving immeasurable destruction of unprecedented magnitude in its wake. Worth mention that cyclone Eloise hit the country when it was coping with the harmful effects of the Covid-19 pandemic. To date, there has been little research that has been conducted on socio-environmental impacts of cyclones in this region. Furthermore, climate change is projected to increase the frequency and intensity of tropical storms. Thus, this study has been designed as initial step towards filling that knowledge and evidence gap. The objective of this research was to investigate socio-environmental impacts caused by tropical cyclones in Sussundenga District. Preliminary, a desk-based study was made, followed by main data collection phase through in-depth interviews and participant observations. The results mapped which areas were the most affected within the district. It was observed that awareness of climate change is low in rural areas and women were more vulnerable to the effects of cyclones Idai and Eloise. Also, it was found that the lack of investment in climate change adaptation actions still pose a great challenge for the country.